The Role and Impacts of Authentic Leadership on Staff Engagement and Performance: A Study among School Leaders and Teachers in Private Schools in the UAE - Samkari, Huda Al (2019)
Authentic leadership is built on ethical foundation. Authentic leaders are positive, honest and promote openness to value the input of the followers. And authentic leadership has positive impacts on staff engagement and performance. This study therefore aimed to explore the role of authentic leadership and the impacts in driving staff engagement and performance. In particular, the research studied the interrelationship of authentic leadership practices of school leaders on school teachers in selected private schools in Dubai, in the United Arab Emirates (UAE). The study used quantitative method gathering data through survey questionnaire among 200 teachers and 45 head-teachers across 4 private schools in Dubai. The data gathered was analysed using descriptive statistical analysis. The findings indicate that authentic leadership plays a crucial role in increasing staff engagement and enhances staff performance, in the schools that were studied. The study recommends that there is a need for effective measures to enhance authentic leadership practices through relevant motivation, development, support and evaluation. School leaders need to be a part of the leadership training programme so that they can develop self-awareness among staff members. School leaders has to collect regular feedbacks of school staffs in the development of school curriculum, pedagogic practices, assessment and other school activities and thereby, improve staff engagement and performance. The study contents that enhanced authentic leadership practices may have enriched impact on staff engagement and performance.